Nasendoscopic Evaluation of the Velopharyngeal Sphincter in Cleft Palate Patinets - Deshpande, S. N. (Indian Journal of Plastic Surgery, 1987)
Nasendoscope was used for evaluation of the function of the velopharyngeal sphincter in twenty-five cleft palate patients using 4% xylocaine as surface anaesthesia. The pattern of closure and the residual defect in velopharyngeal sphincter during speech is helpful in deciding the treatment plan for velopharyngeal insufficiency such as speech therapy or pharyngoplasty.